BIDANG KUASA HIBAH DI MAHKAMAH SYARIAH DI MALAYSIA - Nor Muhamad, Nasrul Hisyam (Jurnal Syariah, 2008)
‘Hibah’ (gift inter vivos) is a matter relating to muslims and regulated by Islamic law. Current situation shows that the principle of hibah is applied in various commercial fields which need to the resolution of the highlighted issues pertaining to the court’s jurisdiction. This article tries to analyze the jurisdiction of Shariah Courts in hearing the hibah cases in Malaysia. The article also discusses the main issues of the matter. The study is based on the relevant statutory, provisions, reported cases as well as the views of some of the authoritative persons in this area.